Attitudes of Prospective EFL Teachers toward Teaching Profession - Thouqan Saleem Masadeh (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
This study aimed to investigate Saudi Pre-service EFL teachers' attitudes toward the teaching profession. Viewpoints of Forty-two student teachers enrolled in the